Gamification tools in mathematics course: students' acceptance / Yee Ming Chew, Kok Shien Ng and Pei Eng Ch'ng - Yee, Ming Chew; Kok, Shien Ng (Universiti Teknologi MARA, Sabah, 2022)
Recently, many scholars have been drawn to the use of gamification in education to promote learners' engagement and improve their learning outcomes. Gamification is regarded as a novel technology-based teaching and learning tool that promotes learning in a fun and engaging manner. Using the modified technology acceptance model (TAM) as its theoretical foundation, the present study is designed to investigate the students' acceptance of the use of gamification to support their mathematical learning during open and distance learning (ODL). Free online gamification tools were designed for a mathematics course, namely, Further Differential Equations. A sample of 49 civil engineering degree students was selected to participate in this study for using gamification tools. The primary research methodology applied in this study was a quantitative approach based on a modified TAM survey questionnaire. The questionnaire results were analysed using descriptive statistics, independent samples t-test and correlation analysis. The analysis was focused on four proposed determinants, namely perceived usefulness, perceived ease of use, attitude towards using, and behaviour for intention to use. Findings revealed no statistical differences between male and female groups on all four determinants proposed in modified TAM's model. Also, the study discovered significant positive relationships among all of the model's determinants on gamification acceptance.